The indigenous microbial diversity involved in the spontaneous fermentation of red dragon fruit (Hylocereus polyrhizus) identified by means of molecular tools - Lim, Teck Wei; Choo, Kah Yee; Lim, Renee Lay Hong; Pui, Liew Phing; Tan, Chin Ping; Ho, Chun Wai (Elsevier, 2023)
Red dragon fruit (RDF) is well-known for its high nutritional content, especially the red pigment betacyanins that possess high antioxidant activity. Natural fermentation is an ancient yet outstanding technique that relies on the autochthonous microbiota from fruits and vegetables surfaces to preserve and improve the nutritional values and quality of the food product. The present study was to evaluate and identify the indigenous microbial community (bacteria and fungi) that are involved in the natural fermentation of RDF. Results revealed a total of twenty bacterial pure cultures and nine fungal pure cultures were successfully isolated from fermented red dragon fruit drink (FRDFD). For the first time, the PCR amplification of 16S rRNA and ITS regions and sequence analysis suggested nine genera of bacteria and three genera of fungi (Aureobasidium pullulans, Clavispora opuntiae, and Talaromyces aurantiacus) present in the FRDFD. Four dominant (≥10 % isolates) bacteria species identified from FRDFD were Klebsiella pneumonia, Brevibacillus parabrevis, Bacillus tequilensis and Bacillus subtilis. The carbohydrate fermentation test showed that all the indigenous microbes identified were able to serve as useful starter culture by fermenting sucrose and glucose, thereby producing acid to lower the pH of FRDFD to around pH 4 for better betacyanins stability. The present study provides a more comprehensive understanding of the indigenous microbial community that serves as the starter culture in the fermentation of RDF. Besides, this study provides a useful guide for future research to be conducted on studying the rare bacterial strains (such as B. tequilensis) identified from the FRDFD for their potential bioactivities and applications in medical treatment and functional foods industries.